Hubungan Pengetahuan Remaja Dengan Perilaku Pencegahan Gastritits Di Sma Negeri 5 Tuban - Pratiwi, Alvinda; Sumiatin, Titik; Su’udi, Su’udi (Peneliti.net, 2024)
Gastritis is still a social and public health problem in both developed and developing countries. According to several surveys, gastritis is more common in adolescents. One of the factors that causes gastritis is the lack of knowledge and awareness about the importance of maintaining stomach health, this is a risk for doing habits that trigger gastritis, causing inflammation in the stomach. The purpose of this study was to find out how the knowledge of adolescents with gastritis prevention behavior at SMA Negeri 5 Tuban. The design of this study used correlation with a cross sectional approach. The sample in this study were all 121 students of SMA Negeri 5 Tuban. The sampling technique used is simple random sampling. The independent variable in the research is the knowledge of adolescents. The dependent variable in this study is gastritis prevention behavior. How to collect data with a questionnaire in the form of google form then do the data processing and tested using the chi-square test. Based on the statistical test results obtained (p = 0.04 <0.05) showed that there was a significant relationship between adolescent knowledge and how to prevent gastritis, with the results that most students had knowledge in the good category 51.2% and almost all students had gastritis prevention behavior in the sufficient category as much as 79.3%. It is expected that respondents can find out the behavior of preventing gastritis by adjusting their diet of foods that can cause stomach pain, such as spicy, sour, and fatty foods, while also avoiding excessive stress.